Effects of Fermented Sea Tangle Supplementation on the Oxidative Stress and DNA Damage in Older Women - Byeong Hwan Jeon (Asian Society of Kinesiology, 2019)
OBJECTIVES The free radical theory of aging posits that a decrease in antioxidant capacity occurs in old age. This exposes the body to greater oxidative stress, which has been reported to have a causal effect on the aging process and development of disease. Sea tangle is a fermented food source shown to provide a reducing antioxidant effect. METHODS Forty senior women participated in a randomized, double-blind, and placebo-controlled study. Two groups were formed, one placebo (74.57 ± 5.69 yrs) and one FST (fermented sea tangle) group (72.35 ± 5.54 yrs), which received 1.5g/day of FST for 6 weeks. RESULTS Serum superoxide dismutase (SOD), glutathione peroxidase (GPX), glutathione reductase (GSR), thiobarbituric reactive species (TBARS) and 8-hydroxodeoxyguanosine (8-OHdG) levels were analyzed before and after the experimental period. FST supplementation significantly increased serum SOD and GSR levels. Whereas, levels of oxidative stress markers, TBARS and 8-OHdG were significantly decreased in comparison to those in the placebo group, after 6 weeks. CONCLUSIONS Our results suggest that FST can act as an effective exogenous antioxidant intervention against the dwindling efficiency of our biological defenses and/or increased intracellular reactive oxygen and DNA damage levels, associated with aging.